1974
DOI: 10.1042/bj1430435
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of equilibrium constants by affinity chromatography

Abstract: Theoretical expressions are derived for affinity chromatography of systems comprising an acceptor A with one binding site for attachment to a functional group X on the column matrix and one site for interaction with a small ligand B that specifically affects its elution. From a general relationship covering all possible interactions between A, B and X simpler expressions are derived for affinity systems in which only two equilibria operate. Methods are suggested whereby these simpler systems may be characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
71
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 139 publications
(75 citation statements)
references
References 19 publications
4
71
0
Order By: Relevance
“…2A) diverges from the linear calibration plot. This relative retardation is consistent with enzyme migration governed by a superimposed protein−matrix interaction on the size-exclusion process, the phenomenon responsible for the retarded elution of lysozyme from Sephadex matrices [17]. Vertical displacement of the elution volumes for the other three protein standards to account for enzyme retardation leads to the revised calibration plot (open symbols and solid line) (inset (Fig.…”
Section: Size-exclusion Chromatography Ofsupporting
confidence: 66%
“…2A) diverges from the linear calibration plot. This relative retardation is consistent with enzyme migration governed by a superimposed protein−matrix interaction on the size-exclusion process, the phenomenon responsible for the retarded elution of lysozyme from Sephadex matrices [17]. Vertical displacement of the elution volumes for the other three protein standards to account for enzyme retardation leads to the revised calibration plot (open symbols and solid line) (inset (Fig.…”
Section: Size-exclusion Chromatography Ofsupporting
confidence: 66%
“…NaCl was included in the elution buffer to reduce ionic interactions between the protein and the column matrix, although it was realised this might increase hydrophobic interactions 27 . Glucose was used since it had been used in the elution buffer for the purification of lysozyme on Sephadex G-100 23 . Lysozyme gave uncharacteristically high elution volumes, leading to underestimates of its known molecular weight when glucose was omitted from the elution medium.…”
Section: (-7'977-32mentioning
confidence: 99%
“…The first problem tackled was the development of a set of quantitative expressions for the characterisation of all possible combinations of solute-matrix, solute-ligand and matrix-ligand interactions by quantitative affinity chromatography (Nichol et al 1974), a technique introduced by Don in conjunction with Pat Andrews (University of Reading) the year before. A solution to the problem of allowance for the effects of osmotic gel shrinkage on the characterisation of protein self-association by gel chromatography then followed (Baghurst et al 1975).…”
Section: A 12-month Sabbatical In Oxfordmentioning
confidence: 99%
“…Initially, this behaviour was attributed (somewhat intuitively) to spatial considerations, which suggested that further acceptor attachment after the initial event was unlikely to occur (Nichol et al 1974). This potential paradox was resolved by quantitative solution to the problem of acceptor multivalence in its interaction with matrix-bound affinity sites Winzor et al 1982), a problem solved initially by means of Flory reacted-site probability theory but later handled using a different approach (Lollar and Winzor 2014).…”
Section: Quantitative Affinity Chromatographymentioning
confidence: 99%